If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-11y-6=11-8y
We move all terms to the left:
-11y-6-(11-8y)=0
We add all the numbers together, and all the variables
-11y-(-8y+11)-6=0
We get rid of parentheses
-11y+8y-11-6=0
We add all the numbers together, and all the variables
-3y-17=0
We move all terms containing y to the left, all other terms to the right
-3y=17
y=17/-3
y=-5+2/3
| 4(-x+1)+3=-2(x+1) | | 5w+15=105 | | -11y-6=2-8y | | 15x+2=10x+23 | | (2)1-x=5 | | -5(8n+6)=36+7n | | -92=-8+2(6x+6) | | (4)1-x=5 | | 0(2y+2)−y=2(8y−8) | | 7(-3b+3)=-8+8b | | m∠1+117+33=180 | | 12x+7×=312 | | 4(1/3x+8)=12x | | 0=(2x)(24-2x)(18-2x) | | 1.6/1=y/1.6 | | (x-3)(x+4)-18=0 | | b/4+4=20 | | 2x-2x+4=6 | | D=(-7/5)t+22 | | 3x-7x=-4+5-11 | | -2(-v2)=-3-2v | | 3x/4+7x/8=36 | | 3x+5x=100 | | Y2-16x=0 | | 3x+11=16x= | | 2-3x-4=4 | | 9y+2+2y+3+15y-27=180 | | 0.45=0.03x+.15 | | -7(4+4p)+6=3-3p | | 9=-3x+9-6x+6 | | 26x+5=28x-1 | | 6x+35+9x=15(x+4)-24 |